Anti-Leukemic Effects of Typhonium Flagelliforme on Human Lymphoblastoid Cells (CEMss) and Murine Leukemic (WEHI-3) Model - Syam Mohan, Murali Mohan (2010)
To date, there has been no literature reported on the mechanism of Typhonium flagelliforme and its effects on leukemia. Hence, the anti-leukemia effect of Typhonium flagelliforme was investigated in vitro and in vivo leukemic model. Extraction and fractionation using organic solvents were applied to obtain fractions from T. flagelliforme and subsequently, chemical analysis was done using GC-MS. In vitro cytotoxic effects of extracts and fractions were tested in several human cancer cell lines including leukemia (CEMss cells) using MTT assay. Various microscopy techniques were used to study morphological changes occurring during treatment. The Annexin V assay, TUNEL assay, cell cycle analysis and DNA laddering were employed to detect apoptosis. Colourimetric assays for caspase-3 and 9, immunoblot analysis for cytochrome c, BcL-2, PARP, FasL and β-actin were analysed. The in vivo model of leukemia was induced in male BALB/c mice using WEHI-3 cells. The DCM extract of the plant tuber was used for treatment at various doses. Amongst 8 plant extracts investigated, the dichloromethane (DCM) extracts of T. flagelliforme tuber demonstrated low and significant anti proliferative effect against both CEMss (6.5±0.4 μg/ml) and WEHI-3 cells (24.0±5.2 μg/ml) (p<0.05). Further fractionation of the DCM tuber extract resulted into 12 fractions. Seven of these 12 fractions showed significant cytotoxicity against CEMss, in which the DCM/F7, DCM/F11 and DCM/F12 fractions showed highest anti-cancer activities of 3.0, 5.0 and 6.2 μg/ml respectively. Further studies of these fractions towards non cancerous Peripheral Blood Lymphocytes (PBL) exhibited significant selectivity of DCM/F7 compared to other fractions. Phytochemical analysis using GC-MS revealed that the DCM/F7 fraction contains linoleic acid (51.20%), n-hexadecanoic acid (17.89%), 9-hexadecanoic acid (6.99%) and Stigmasta-5,22-dien-3-ol (6.06%). Cytological observations exhibited chromatin condensation, cell shrinkage, abnormalities of cristae, membrane blebbing, cytoplasmic extrusions and formation of apoptotic bodies, further confirmed using AO/PI, SEM and TEM analysis. The Annexin V and TUNEL assay revealed apoptotic induction in CEMss cells exposed to the DCM/F7 in a time-dependent manner, whilst DNA fragmentation of CEMss cells were detected using 1.0% agarose gel electrophoresis. The DCM/F7 fraction significantly (p<0.05) stimulated both caspases 3 and 9 activities. The immunoblot results revealed that DCM/F7 caused the release of mitochondrial cytochrome c and cleaved 116 kDa PARP into 85 kDa fragments. The Bcl-2 protein was found to decrease during treatment. Meanwhile, FasL did not exhibit up or down regulation on treatment. Cell cycle analysis revealed that there is significant (p<0.05) G1 phase arrest in a time-depended manner. The DCM extract of T. flagelliforme tuber in vivo markedly inhibited the proliferation of WEHI-3 in male BALB/c mice as evidenced by reduction in the percentage of immature monocytes as well as granulocytes, liver weight, spleen weight and histopathological profiles of H&E stained spleen tissue. The DCM tuber extract of T. flagelliforme significantly decreased the spleen tumor size, which had dose-dependent effects. Sections of spleen tissue of the BALB/c mice treated with the extract. Treatment at 800 mg/kg dose showed evidence of apoptosis in comparison to the control groups. Collectively, results presented in this study demonstrate that T. flagelliforme, a local herbal medicinal plant in Malaysia inhibited the proliferation of leukemia in vitro selectively, leading to the programmed cell death, which was later confirmed to lead through mitochondrial pathways. Moreover, in vivo study on an orthotopic BALB/c mice model clearly shows that, T. flagelliforme tuber extract has inhibited the proliferation of leukemia via the induction of apoptosis.